A Systematic Review of Treatment Strategies for the Prevention of Junctional Complications After Long-Segment Fusions in the Osteoporotic Spine. Issue 5 (June 2021) - Echt, Murray; Ranson, William; Steinberger, Jeremy; Yassari, Reza; Cho, Samuel K.
Study Design: Systematic review Objectives: Proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) are well-known complications after long-segment fusions in the thoracolumbar spine of osteoporotic patients. Recent advances in anti-resorptive and anabolic medications, instrumentation, surgical technique, and cement augmentation have all aided in the avoidance of junctional kyphosis. In this article, current literature on the prevention of PJK and PJF in the osteoporotic spine is reviewed. Methods: A systematic literature review was conducted using the PubMed/MEDLINE and Embase databases in order to search for the current preventive treatment methods for PJK and PJF published in the literature (1985 to present). Inclusion criteria included (1) published in English, (2) at least 1-year mean and median follow-up, (3) preoperative diagnosis of osteoporosis, (4) at least 3 levels instrumented, and (5) studies of medical treatment or surgical techniques for prevention of junctional kyphosis. Results: The review of the literature yielded 7 studies with low levels of evidence ranging from level II to IV. Treatment strategies reviewed addressed prophylaxis against ligamentous failure, adjacent vertebral compression fracture, and/or bone-implant interface failure. This includes studies on the effect of osteoporosis medication, cement augmentation, multi-rod constructs, and posterior-tension band supplementation. The role of perioperative teriparatide therapy maintains the highest level of evidence. Conclusions: Perioperative teriparatide therapy represents the strongest evidence for preventive treatment, and further clinical trials are warranted. Use of cement augmentation, sublaminar tethers, and multi-rod constructs have low or insufficient evidence for recommendations. Future guidelines for adult spinal deformity correction may consider bone mineral density–adjusted alignment goals.